Features and Function of Woman Language Found in The La La Land Film: A Sociolinguistics Study - Masayu Miranda Balqis; Puspita Sari (Jurnal Sinestesia, 2023)
This research aims to examine the features and functions of women's language, according to Lakoff's theory, as demonstrated by the main female character in the film "La La Land." Data about the speech of the characters are collected through documentation by following several steps. The first step is to watch the film to understand its content. this initial stage is carried out through observation of film recordings on Netflix. The second step is to identify, researchers begin to carefully determine the features and functions of the female language of conversation between men and women. The third step is to classify, the identification results are then classified into two more structured categories to facilitate further data analysis. for features and functions of female language using Lakoff theory. The fourth step is analyzing data that has been collected and then analyzed involves the process of removing data that is less relevant and then converting raw data to a format more suitable for analysis. It also uses qualitative and descriptive methods. through the pronunciation of words by the female characters in the film "La La Land". The conclusion of this study is that there are 10 characteristics and features of female language, namely: lexical hedges, tag questions, rising intonations, empty adjectives (2), intensifiers, super polite (2), and swear words (2).